The Result of Improving The Organizational Performance For Cairo University Hospitals Through The Strategy Of Simplification - Abdulhamed, Mohamed Essam Eldin Bahy Eldin; Al-Sayed, Khaled Qadri (Journal of Economic, Administrative and Legal Sciences, 2022)
The main objective of the research was to determine the Effect of improving the organizational performance of hospitals through the application of the simplification strategy, with analyzing the impact of improving organizational performance represented in (operational performance, financial performance), for hospitals through the application of the simplification strategy represented in (the added value from the point of view of the customer, Getting rid of waste), presenting findings and recommendations to decision makers in Cairo University hospitals that pursue the idea of improving organizational performance through the application of the strategy. Single staff, represented by (doctors, nursing, administrators) in hospitals.The results concluded that the hospital takes into account its concern for the safety of workers from infection, and balances between what the client pays, and the level of service provided, in addition to providing the service in proportion to the expectations of the client, identifying wastage in transportation and unnecessary movement to get rid of it, and avoiding wasting human resources in other ways. The appropriate function for it is through a culture of creativity and innovation, so that the administration can reduce the stages of consumables by recycling waste again. In addition to the keenness to take the customer’s opinion about the service provided, and the need for the hospital administration to achieve a balance between the service and the planned time to avoid overworking the workers.
Keywords: organizational performance; simplification strategy; added value from the customer's point of view; eliminating waste; operational performance; financial performance; Cairo University Hospitals